Karakteristik, Pengetahuan, dan Sikap Ibu terhadap Penyakit Demam Berdarah Dengue - Herke J. O. Sigarlaki (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Dengue Haemorragic Fever (DHF) is an illness that we can find in children an adult with the main simptoms such as fever, myalgia which is could be worst after 2 days. Prevention of DHF is organized with health promotion and treatment education for doctors and paramedic and also the involvement of people to eliminate the mosquitos, so we hope at the future the prevalence of DHF could be decreased.Objective: To get information about the distribution of characteristic and behavior of mother toward DHF. The characteristics include age, occupation, and education. While behaviors includes attitude, knowledge, and practice.Method:  We use a cross sectional descriptive for study with a questioner and check list as the instrument.Result: From this study we found that 46,4 % of the subject lacked of knowledge about DHF ; 42,5% lacked of knowledge as well as low education. 44,1% lack of knowledge with good attitudeConclusion: The level of education contributes in determining the level of knowledge while knowledge does not always determine that person’s attitude.Keywords: Dengue Haemorragic Fever (DHF), characteristic, knowledge, behavior, attitude